Factors affecting adoption of improved management practices in the pastoral industry in Great Barrier Reef catchments. (1st July 2015) - Rolfe, John; Gregg, Daniel
Abstract: Substantial efforts are being made by industry and government in Australia to reduce adverse impacts of pastoral operations on water quality draining to the Great Barrier Reef. A key target is to achieve rapid adoption of better management practices by landholders, but current theoretical frameworks provide limited guidance about priorities for improving adoption. In this study information from direct surveys with landholders in the two largest catchments draining into the Great Barrier Reef has been collected and analysed. Study outcomes have important implications for policy settings, because they confirm that substantial variations in adoption drivers exist across landholders, enterprises and practices. The results confirm that the three broad barriers to adoption of information gaps, financial incentives and risk perceptions are relevant. This implies that different policy mechanisms, including extension and incentive programs, remain important, although financial incentives were only identified as important to meet capital and transformational costs rather than recurrent costs. Highlights: Tested adoption of management practices in Great Barrier Reef grazing catchments. High adoption rates of better practices needed to reduce impacts on reef. Variations in drivers exist across landholders, enterprises and practices. Information, financial and risk issues are main barriers to adoption. Mix of policy mechanisms required to address diversity of drivers.